The determinants for sustainability in a low-technology SME textile cluster in an emerging economy. (2018) - Venugopal, Pingali; Malhotra, Ritu; Annamalai, Balamurugan
The purpose of this paper is to ascertain whether cluster-based strategies for SMEs could result in the enhancement of competitiveness in an environment of a developing nation, with a primary objective of examining the use of a cluster approach as a tool for sustainability – particularly for a low-technology textile cluster. Building on extensive literature dealing with SME clusters and cluster-based strategies, the paper identifies the determinants and variables for SME cluster sustainability in philosophy and policies. The paper builds upon and links together research about collective efficiency in small-industry clusters and literature about entrepreneurial environments, the significance of cluster policy and intermediaries, trust, and the acquisition of technological capabilities in context to low-technology textile clusters of an emerging economy. The paper identifies the different advantages that commonly occur in a typical cluster and then examines the ways in which these advantages may boost competitiveness, resulting in sustainability. Theoretical insight from the literature about clustering, agglomeration advantages, skill, trust, and competitiveness in developing and advanced economies is examined in order to make the assessment. Subsequently, solutions for the future have been proposed by means of a conceptual framework. Generation of hypotheses for further empirical validation are proposed.